"This Ruins Lives": Using Monopoly© to Understand the Prison Industrial Complex. Issue 3 (3rd July 2022) - Shah, Rita
Abstract: Monopoly ©, the classic board game that celebrates capitalism, has been used in a variety of classes to help students understand concepts such as the impact of systemic racism on generational wealth and global inequality. In this article, I explore the use of a modified version of Monopoly © to explain the prison industrial complex (PIC). In reviewing post-game evaluations, I find the game is a fun in-class activity that helps students better understand the financial interests private industries have in the prison system and the impact of the PIC on incarcerated individuals. I also discuss suggestions for improving the game as a pedagogical tool, as well as limitations it poses as a classroom activity.